VACCINATION AGAINST HUMAN PAPILLOMAVIRUS FOR PREVENTION OF CERVIX UTERI CANCER IN PAKISTAN -A PUBLIC HEALTH PERSPECTIVE AND DEBATE - Badar, Farhana (Journal of Ayub Medical College Abbottabad, 2011)
Dear Editor, In many regions of the world, a vaccination program against the Human Papilloma Virus (HPV), to prevent the cancer of the cervix uteri, has been implemented. This is due to a relatively high prevalence of Human Papilloma Virus, which is implicated in aetiology of cervical cancer. As estimated by Globocan, in 2008, per 100,000 women, in very high incidence regions as SubSaharan Africa, the annual age-standardised incidence went up to 56.3 and mortality to 41.7. The incidence of cancer of the cervix uteri was also reported to be high in South America (23.9) and Melanesia (23.0). However, in Pakistan, the estimates for cervical cancer were relatively low with an incidence of 19.5 (11,688 cases) and mortality of 12.9 (7,311 deaths), per 100,000 women. A meta-analysis of 194 studies comprising 1,016,719 women with normal cytological findings has demonstrated that globally, among women, the cervical HPV prevalence is around 11.7%; in Sub-Saharan Africa it is 24%; in Eastern Europe 21.4%; and in Latin America 16%.1 These are considered to be highprevalence areas. The results with type-specific HPV data (n=215,568) have illustrated that the 5 most common types worldwide are HPV-16 (3.2%), HPV-18 (1.4%), HPV-52 (0.9%), HPV-31 (0.8%), and HPV-58 (0.7%).1 In contrast, a recent study from Pakistan has shown that in women 15-59 years of age, the prevalence of HPV is 2.8% (n=899) and 92.2% (n=91) in general population and in women with invasive cervical cancer, respectively.2 Also, the same study has reported that, in general population, the HPV-16 prevalence is 0.7%; and in those with cervical cancer, the HPV-16 prevalence is 75.8% and HPV-18 is 6.6%. Some other studies from the country have revealed that the HPV prevalence is between 18% and 98% (n=50- 162).3-5 Statistics on the prevalence of HPV infection in the non-neoplastic samples from the general population of Pakistan are sparse. So is the information on distribution of HPV types and costs in terms of screening, diagnosis, and treatment of the HPVassociated diseases. Corroborating research that would support initiating a vaccination program against Human Papilloma Virus in this type of population is clearly lacking. The research questions that are unanswered need to be addressed promptly taking into account the socio-cultural and religious norms of the society. Accordingly, there is a need to conduct more studies on both the neoplastic and non-neoplastic samples from our population, and populations similar to ours, so as to identify cervical cancer risk factors before vehemently advocating the adoption of preventive measures against HPV infection, including vaccination. Farhana Badar and Natasha Anwar